"It made me feel Brazilian!": Addressing prejudice through Capoeira classes in a school in Western Australia. (23rd November 2018) - Radicchi, Marcelo Rocha; Papertalk, Lennelle; Thompson, Sandra
Abstract: Issue addressed: Social inclusion is important for mental health, and schools are important settings for creating positive attitudes against prejudice. Capoeira is a Brazilian traditional culture that is a mixture of dance, martial arts and games, and has many educational possibilities. Since it arose from and helped people rise above black oppression, the purpose of the project was introducing the content of capoeira to primary school students with the aim of promoting of mental health and preventing prejudice behaviours using an intercultural perspective in a school where nearly half the students are Aboriginal. Methods: Five capoeira classes were conducted in a primary school located in a regional city in Western Australia, with two Year 5‐6 classes and boys and girls aged 11‐12 years old. Activities were meant to create an environment of dialogue, joy and empathy towards a different culture. Feedback from 31 of 34 students were collected and analysed, dealing with their impressions, positive and negative aspects. Results: The results were positive, with aspects of movement, joy, dance and music identified as important experiences. Empathy towards the new culture was written and drawn by many of the students. Joint work with teachers improved engagement and feedback from students. Conclusion: Capoeira can be an inspiring vehicle in intercultural education, promoting mental health and empathy for different cultures. So what?: Broad intercultural education which embraces positive cultural experiences and stories from elsewhere, delivered in schools can contribute to children's intercultural competence. Longer interventions with follow‐up to measure changes in students' attitudes are required.